A Qualitative Exploration of the Psychological Meaning of Body Piercing in Women. - Hunt, Justine (My University, 2007)
The central aim of this research was to ascertain the psychological meaning of, and motivation for body piercing in a sample of female body modifiers. It was decided to conduct research on the psychology of body piercing because although medical, anthropological and social research has been conducted into piercing practices and body modification, very little has focused on the underlying psychological meanings and motivations associated with body modification. Furthermore, the focus of this study was limited to women because it was felt that had both genders been included, possibly gender based differences would have caused the scope of the research project to become too wide. By focusing specifically on women, it was felt that a deeper understanding of the underlying psychological motivations for the piercing of the female body could be explored. For the purposes of this research, the operational definition of body piercing is defined as that which does not echo mainstream fashion trends or promote Eurocentric, socially sanctioned ideals of beauty. The participants needed to have pierced body parts (excluding their earlobes), and the piercings or the piercing process should hold specific significance and meaning for them. Participants who had pierced body parts only for aesthetic reasons were excluded from this study. Those who were included attributed more than just a decorative function and aesthetic value to their body piercings. In other words, they deviated from mainstream piercing practices in terms of the meanings they attach to their piercings. Some of the piercings and piercing practices and processes undertaken by the participants represent a departure from the ‘norm’, and have been described as bordering on pathological. The research sought to identified commonalities and differences amongst the participants and to understand their experiences and behaviour within the context of psychodynamic feminist frameworks. Broadly defined, feminism is a movement organized around the belief that men and women are/should be socially, politically and economically equal. Contemporary feminism, which influences perceptions of female body modification, is split into two distinct strands: one school of feminism views body modification as a form of self-injury and self-mutilation while the other holds that it is a positive resistance in the face of gender norms (Pitts, 2003). This was taken into account in this study. Given that the participants were all women, and that the relationship between body modification and social structures of power/authority are a central concern in feminist literature (Atkinson, 2002), this paradigm was chosen because it provides an appropriate and relevant framework within which to explore the underlying motives and meaning of body piercing for female body piercers. Their attitudes, meaning making processes and relationships with their bodies in relation to their piercings are used to uncover the significance of their body projects and their decisions to be pierced. The central themes which emerged through the thematic data analysis are related back to the feminist literature. Psychoanalysis explores repressed or unconscious impulses, object relations, anxieties, and internal conflicts. For this reason, a psychodynamic framework was used to provide a context within which to explore the unconscious motivations, anxieties and defenses employed by the participants. Freud’s theories of masochism are examined in an attempt to further understand the female body piercer. These are placed within a general psychodynamic framework, and the works of Bowlby, Fonagy, Kernberg, Malan and Winnicott are used to support the findings of the research. The research is based in the qualitative paradigm, with the aim of exploring and describing the body modifier’s thoughts, fantasies, feelings and experiences around being pierced. The data gathered was analyzed using thematic content analysis to elucidate the participants’ reasons for choosing to modify their bodies, and to highlight the meanings of these practices in the context of the their personal histories. In total, six participants were interviewed, although one interview was not included for analysis as it was felt that the data gathered from this interview, while not contradicting the rest of the data gathered, was superficial in content and did not contribute to the research. The excluded participant spoke very broadly and did not really offer much personal information as to the meaning and motives behind her piercings. The research explored the history of body modification, definitions of body modification and body projects, issues pertaining to identity, body image and self concept, expanded consciousness and altered states of being, pain and sadomasochism, the pathologizing of body modification, feminist perspectives on body modification and psychodynamic explanations for body modification. Although much literature abounds on body modification practices, very little is of academic significance. Furthermore, few studies have been conducted into this area from a psychological perspective. In this regard, the writings of Favazza (1996), Featherstone (2003) and Vale & Juno (1989) were used to provide a context within which to place this study. Research papers by Atkinson (2002) and Dennes (2005) also proved particularly useful, and will be discussed in the following chapter.
Student Number : 9304796E - MA research report - School of Psychology - Faculty of Humanities
Keywords: body piercing; body modification; self harm; self mutilation; body image; feminism and body